2015
DOI: 10.1016/j.jphs.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TRPM2 in a wide range of inflammatory and neuropathic pain mouse models

Abstract: Recent evidence suggests a role of transient receptor potential melastatin 2 (TRPM2) in immune and inflammatory responses. We previously reported that TRPM2 deficiency attenuated inflammatory and neuropathic pain in some pain mouse models, including formalin- or carrageenan-induced inflammatory pain, and peripheral nerve injury-induced neuropathic pain models, while it had no effect on the basal mechanical and thermal nociceptive sensitivities. In this study, we further explored the involvement of TRPM2 in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Intraplantar injection of H 2 O 2 caused brief nociceptive pain [19], but specific subcutaneous versus deep tissue injections were not studied and would be difficult in such small spaces like the hind paw. In other previous studies, after intraplantar injection of H 2 O 2 , nociceptive behavior was short-lasting (< 5 min), which is consistent with our finding after subcutaneous injection over the gastrocnemius [30, 33, 34]. In humans, cutaneous wounds are frequently flushed or rinsed with much higher concentrations of H 2 O 2 (880 mM concentration of commercially-available 3% H 2 O 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Intraplantar injection of H 2 O 2 caused brief nociceptive pain [19], but specific subcutaneous versus deep tissue injections were not studied and would be difficult in such small spaces like the hind paw. In other previous studies, after intraplantar injection of H 2 O 2 , nociceptive behavior was short-lasting (< 5 min), which is consistent with our finding after subcutaneous injection over the gastrocnemius [30, 33, 34]. In humans, cutaneous wounds are frequently flushed or rinsed with much higher concentrations of H 2 O 2 (880 mM concentration of commercially-available 3% H 2 O 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Microglial/Macrophagic TRPM2 Channels in Neuropathic Pain TRPM2 is thought to be involved in a range of pathological pain states, including neuropathic pain. 31,36,37) Evidence suggests that peripheral and spinal neuroinflammation mediated by the interaction between nociceptive neurons and immune/glial cells plays a pivotal role in neuropathic pain. 38) After peripheral nerve injury, pro-nociceptive inflammatory mediators, such as pro-inflammatory cytokines, chemokines, and excess ROS produced by peripheral tissues and the spinal cord, can lead to peripheral and central sensitization of nociceptive neurons.…”
Section: Physiological Roles Of Trpm Channels In Gliamentioning
confidence: 99%
“…36) Consequently, TRPM2 is involved in a wide range of pathological pain states induced by peripheral and spinal neuroinflammation-such as inflammatory pain, osteoarthritic pain, neuropathic pain induced by peripheral nerve injury, chemotherapy-induced peripheral neuropathy, and painful diabetic neuropathy-rather than in physiological nociceptive pain. 37) …”
Section: Physiological Roles Of Trpm Channels In Gliamentioning
confidence: 99%
“…TRPM2 also activates ERK MAPK and induces nuclear translocation of NFκB, resulting in production of proinflammatory cytokines and chemokines [76,77,81,83,84]. Consequently, pharmacological and genetic studies have demonstrated that TRPM2 contributes to inflammatory and neuropathic nociceptive hypersensitivity [7779,82,85]. …”
Section: Mechanisms Of Nitroxidative Signaling In Neuronal Hyperexcitmentioning
confidence: 99%